Scale-Dependent Turbulent Dynamics and Phase-Space Behavior of the Stable Atmospheric Boundary Layer - Francesco Carbone; Tommaso Alberti; Luca Sorriso-Valvo; Daniele Telloni; Francesca Sprovieri; Nicola Pirrone (Atmosphere, 2020)
The structure of turbulent dynamics in a stable atmospheric boundary layer was studied by means of a phase-space description. Data from the CASES-99 experiment, decomposed in local modes (with increasing time scale) using empirical mode decomposition, were analyzed in order to extract the proper time lag and the embedding dimension of the phase-space manifold, and subsequently to estimate their scale-dependent correlation dimension. Results show that the dynamics are low-dimensional and anisotropic for a large scale, where the flow is dominated by the bulk motion. Then, they become progressively more high-dimensional while transiting into the inertial sub-range. Finally, they reach three-dimensionality in the range of scales compatible with the center of the inertial sub-range, where the phase-space-filling turbulent fluctuations dominate the dynamics.